2012
DOI: 10.1088/0004-637x/749/1/27
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of the Solar Magnetic Field: Polarity Reversals, Butterfly Diagram, and Quasi-Biennial Oscillations

Abstract: The spatio-temporal dynamics of the solar magnetic field has been investigated by using NSO/Kitt Peak magnetic synoptic maps covering the period 1976 August-2003 September. The field radial component, for each heliographic latitude, has been decomposed in intrinsic mode functions through the Empirical Mode Decomposition in order to investigate the time evolution of the various characteristic oscillating modes at different latitudes. The same technique has also been applied on synoptic maps of the meridional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 48 publications
6
54
1
Order By: Relevance
“…The intrinsic timescales found in these IMFs seem to match once more those pertaining to the so-called quasi-biennial oscillations (QBOs) that have been observed in solar activities and proxies with periodicities between 0.6 and 4 years (Bazilevskaya et al, 2015;Kolotkov et al, 2015;Vecchio et al, 2012), as well as in meteorological data like Harrison (2008) who identifies a 1.68-year peak in cloud cover or high-latitude stratospheric temperatures and geopotential heights (Labitzke and Loon, 1988). Nevertheless, within the scope of the current analysis, the interpretation of these lowfrequency variability components as a real, possibly QBOlike, signal is uncertain.…”
Section: The Intrinsic Timescales Of Variability In the Ssisupporting
confidence: 52%
“…The intrinsic timescales found in these IMFs seem to match once more those pertaining to the so-called quasi-biennial oscillations (QBOs) that have been observed in solar activities and proxies with periodicities between 0.6 and 4 years (Bazilevskaya et al, 2015;Kolotkov et al, 2015;Vecchio et al, 2012), as well as in meteorological data like Harrison (2008) who identifies a 1.68-year peak in cloud cover or high-latitude stratospheric temperatures and geopotential heights (Labitzke and Loon, 1988). Nevertheless, within the scope of the current analysis, the interpretation of these lowfrequency variability components as a real, possibly QBOlike, signal is uncertain.…”
Section: The Intrinsic Timescales Of Variability In the Ssisupporting
confidence: 52%
“…Active latitudes are known features of the solar surface (e.g., Vecchio et al 2012) and have been inferred via photometric transits for other stars as well (Sanchis-Ojeda & Winn 2011;Kirk et al 2016). Lanza et al (2011) find that spots near ≈ 30…”
Section: Discussion and Summary Of Contrast Resultsmentioning
confidence: 99%
“…Each IMF is characterized by a typical timescale τ j , defined as the average time difference between local extrema of ψ j . More details about the iterative process used to calculate the IMFs can be found in Vecchio et al (2010Vecchio et al ( , 2012a. This kind of decomposition is local, complete, and orthogonal (Huang et al 1998;Cummings et al 2004).…”
Section: Data Used and Methods Of Investigationmentioning
confidence: 99%
“…As a consequence, the CR intensity shows a pronounced 11 yr variation, with the intensity maximum corresponding almost with the solar activity minimum and vice versa. In addition, many manifestations of solar magnetism, as well as some interplanetary phenomena, show quasi-biennial oscillations (QBOs; see Bazilevskaya et al 2000;Vecchio et al 2012a and references therein), which are also present in CR measurements (e.g., Laurenza et al 2012 and references therein). In particular, it has been shown that the main features of solar activity can be essentially described by superposing QBOs to the ∼11 yr mode (e.g., Vecchio et al 2010;Laurenza et al 2012).…”
Section: Introductionmentioning
confidence: 99%